Temu’s Paradox: Disrupting Markets in Import-Driven and Producing Economies - Maspul, Kurniawan Arif; Putri, Nugrahani Kartika (Jurnal Bisnis dan Komunikasi Digital, 2025)
The rapid expansion of Temu, a global e-commerce powerhouse, is reshaping economic landscapes with profound and often polarizing effects. This study delves into its dual impact on two contrasting economic environments: non-productive economies that thrive on imports with minimal trade barriers (e.g., the Middle East) and producing economies with strong local industries fighting to stay afloat (e.g., Southeast Asia). While Temu’s meteoric rise in import-dependent markets is fueled by tax exemptions and insatiable consumer demand for ultra-affordable goods, its aggressive penetration into producing economies threatens to undermine local industries, displace workers, and disrupt regulatory frameworks. Through a rigorous comparative economic analysis, policy evaluation, and consumer behavior study, this research uncovers the deeper implications of Temu’s business model on market stability, economic sovereignty, and long-term sustainability. The findings shed light on the shifting dynamics of global e-commerce, the effectiveness of protectionist policies, and the socio-economic trade-offs of unrestricted cross-border trade. As nations grapple with the balance between affordability and self-reliance, this study serves as a critical exploration of the policies and strategies that will shape the future of digital commerce in emerging markets.